Herbert's wormhole -Aerostar and the 3 1/2-point plan of vengeance [yet another novel in cartoons] - Nelson, Peter; Rao, Rohitash (Harper / HarperCollins, 2013)
"Herbert, Alex, and Sammie are pretty sure their adventures in the future are over until they meet their greatest villain yet: Sammie's future self, AeroStar, a power-mad tyrant who wants revenge. It's up to our heroes to once again don the mantle of the AlienSlayers and somehow try to save the past, present, and the future from total annihilation"--